How do you solve #-x^2 - 2x + 2 =0# using the quadratic formula?

1 Answer
Oct 15, 2015

Answer:

#x = -3, x = 1#

Explanation:

#-x^2 -2x +2 = 0#

Standard Quadratic Equation:

#ax^2 + bx + c = 0#

a is the constant with x to the power 2.
b is the constant with x to the power 1
c is the constant.

In the given Equation:

a = -1
b = -2
c = 3

Standard Quadratic Formula:

#(-b+-sqrt(b^2 - 4(a)(c))) / (2(a))#
#(-(-2) +-sqrt((-2)^2 - 4(-1)(3))) / (2(-1))#
#(2+-sqrt((4 + 12)) ) / -2#
#(2+-sqrt(16)) / -2#
#(2+-4) / -2#
#(2 + 4) / -2, (2 - 4) / -2#
#6 / -2, -2 / -2#
#x = -3, x = 1#